2012
DOI: 10.1111/j.1600-0781.2012.00651.x
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of sunscreen in human skin after daily applications: a study of sunscreens with different ultraviolet radiation filters

Abstract: Sunscreens accumulate in the skin when applied in the recommended amounts three times daily. In conjunction with other sun protection strategies, sunscreen application on consecutive days prior to UVR exposure can result in a basic skin protection, which may help to prevent severe sunburns on sun holidays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…Therefore, when long periods outdoors are anticipated, the regular application of sunscreens is encouraged (e.g. [ 5 – 7 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, when long periods outdoors are anticipated, the regular application of sunscreens is encouraged (e.g. [ 5 – 7 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Bodekaer et al . showed that when sunscreen was applied three times daily, it accumulated on the skin, increasing exposure to potential skin sensitizers. Thus, exploring if frequent sunscreen application increases the risk for induction of an allergy would be an interesting next step.…”
Section: Discussionmentioning
confidence: 99%
“…Options for UV exposure templates: Like Daavlin, The Copenhagen company Chromo-Light has an MED patch, but it does not seem to be widely available. 5 Daavlin also has a glove and a fabric patch for larger skin areas. 1 MED testing using these options is similar to using the Daavlin sticker patch.…”
Section: Discussionmentioning
confidence: 99%